Estrogen alters adipocyte biology and protects female mice from adipocyte inflammation and insulin resistance - Stubbins, Renee E. (2011)
AIMS: Obesity is associated with insulin resistance, liver steatosis, and low-grade inflammation. The role of estrogen in sex differences in the above comorbidities is not fully understood. Our aim was to assess the role estrogen has in modulating adipocyte size, adipose tissue oxidative stress, inflammation, insulin resistance, and liver steatosis. METHODS: To determine the role estrogen has in the above comorbidities related to obesity, we randomize C57BL/6J mice into four groups (15 mice per group): 1) male, 2) non-ovariectomized female (novx), 3) ovariectomized female (ovx), and 4) ovariectomized female mice supplemented with 17β estradiol (ovx-E2). Mice received either a low-fat or a high-fat diet for 10 weeks. Outcomes measured were bodyweight, body fat, adipocyte diameter, adipose tissue lipolysis markers, adipose tissue oxidative stress, inflammation, insulin resistance, and liver steatosis. RESULTS: Male and ovx female mice consuming the high-fat diet had a higher propensity of gaining weight, specifically in the form of body fat. Estrogen protected female mice from adipocyte hypertrophy and from developing adipose tissue oxidative stress and inflammation. Moreover, novx-female and ovx-female+E mice had higher phosphorylated levels of PKA and HSL, markers associated with lipolysis. Additionally, male and ovx female mice had a higher propensity of developing liver steatosis and insulin resistance. In contrast, estrogen protected female mice from developing liver steatosis and from becoming insulin resistant. CONCLUSION: We show that estrogen protects female mice from adipocyte hypertrophy and adipose tissue oxidative stress and inflammation. Furthermore, estrogen prevented female mice from developing liver steatosis and from becoming insulin resistant.